Seagrass Community of The Coastal In Southern Of Bangka Island, North Minahasa Regancy, North Sulawesi Province - Febry S. I. Menajang; Georis J. F. Kaligis; Billy T. Wagey (Sam Ratulangi University, 2017)
Purpose of this research is to know the community of seagrass, and physical-chemical parameters in the South Bangka island, North Minahasa Regancy, North Sulawesi Province. Data retrieval by the random sampling of systematic method on three lines transect with 50 m long, and 30 quadrants. Data taken in each quadrant is number of species and number of individuals of each species. Results of the measurement of physical and chemical parameters of static waters associated with the feasibility of life for water organisms in it, generally in good condition. Ten species of seagrass have been found in the southern part of the island of Bangka. Four species are always found in any transek i.e Syringodium isoetifolium, Cymodocea rotundata, Enhallus acaroides, and Halophylla ovalis. The highest found in seagrass cover transek 1 i.e. 67.00% while the lowest in transek 3 i.e. 46.30%. Seagrass cover Enhallus acaroides in Bangka island very prominent compared to other species. Based on the current index value is important, Syringodium isoetifolium have a high importance value index only in the transek 3 which means this type of seagrass seagrass types affect other takes part in community level. Ecological index results suggest that the ecosystem of seagrass in Bangka island in the southern part of the State is stable.Keywords: Seagrass, Bangka Island, importance value index (INP). AbstrakTujuan penelitian ini untuk mengetahui komunitas lamun, dan parameter fisik-kimia di bagian Selatan Pulau Bangka; Kabupaten Minahasa Utara, Provinsi Sulawesi Utara. Pengambilan data dengan metode sampling acak sistimatis; pada tiga transek yang diletakkan tegak lurus garis, sepanjang 50 m. Jumlah kuadran yang digunakan sebanyak 30. Data yang diambil dalam setiap kuadran dihitung jumlah jenis dan jumlah individu setiap jenis. Hasil pengukuran parameter fisik statis dan kimia perairan dihubungkan dengan kelayakan hidup bagi organisme air yang ada di dalamnya, umumnya dalam kondisi baik. Telah ditemukan sepuluh spesies lamun di Pulau Bangka bagian selatan. Empat spesies selalu dijumpai di setiap transek yaitu Cymodocea rotundata, Syringodium isoetifolium, Enhallus acoroides, dan Halophylla ovalis. Tutupan lamun tertinggi ditemukan di transek 1 yaitu 67,00 % sedangkan yang terendah di transek 3 yaitu 46,30 %. Tutupan lamun Enhallus acaroides di Pulau Bangka sangat menonjol dibandingkan dengan jenis lainnya. Berdasarkan nilai indeks nilai penting; jenis Syringodium isoetifolium memiliki indeks nilai penting yang tinggi hanya di transek 3 yang berarti jenis lamun ini turut mempengaruhi jenis lamun lainnya dalam tingkat komunitas. Hasil indeks ekologi menunjukkan bahwa ekosistem lamun di Pulau Bangka bagian Selatan dalam keadaan stabil.Kata kunci: Lamun, Pulau Bangka, Indeks Nilai Penting (INP)